Integrated Assessment of Land Capability Classes and Land Damage Status in the Bangsal Sub-watershed - Maroeto Maroeto; Zeti Salsabila Putri Itsnaini; Bakti Wisnu Widjajani; Dinna Hadi Sholikah (Green Engineering Society, 2026)
The Bangsal Sub-watershed is located downstream of the greater Brantas Watershed. It is experiencing problems primarily with poor vegetation cover and high erosion rates. This study aimed to evaluate land capability classes based on land damage status across different land uses. Sampling was carried out purposively at 15 points across five land uses, namely, forests, plantations, dry fields, rice fields and shrublands. The parameters analyzed included the physical, chemical and biological properties of soil. Land capability assessment was conducted based on Arsyad’s work (2010), while damage status was based on the Government Regulation No. 150 of 2000 and the Ministry of Environment Regulation No. 07 of 2006. The results show that the Bangsal Sub-watershed is dominated by land capability classes III to IV with moderate damage status (R.II). Fourteen observation points show moderate damage, and one shows severe damage. The main limiting factors found include porosity, redox potential and permeability. Forest and shrubland land uses show the most stable conditions in terms of all three aforesaid limiting factors. Meanwhile, dry field land use has the most complex limiting factors, including slope, surface rockiness, bulk density, porosity and redox potential. These findings emphasize the importance of matching land use to land capacity to prevent further degradation. Management recommendations include increasing organic matter to improve soil structure, applying contour terraces on sloping terrain to reduce runoff and erosion and developing agroforestry systems to improve soil stability and support watershed sustainability.